Pure spinor superstring partition function - Arroyo Montero, E. A [UNESP] (Universidade Estadual Paulista (Unesp), 2008)
In this thesis, we have calculated the partition function of pure spinors. The computation is performed by using two different methods, namely ghosts-for-ghosts (up to the twelth mass-level) and fixed point (up to the fifth mass-level) techniques. After adding the contribution from the ('qui POT. m, 'teta POT. alfa', 'rô IND. alfa') matter variables, we reproduce the massive open superstring spectrum. Even though pure spinor variables are bosonic, the pure spinor partition function contains fermionic states which first appear at the second mass-level. These fermionic states come from functions which are not globally defined in pure spinor space, and are related to the b ghost in the pure spinor formalism for the superstring

Nesta tese, mostramos o cálculo da função de partição dos espinores puros. O cálculo será executado de dois modos diferentes usando o método de fantasma-para-fantasma (até o décimo segundo nível massivo) e usando o método do ponto fixo (até o quinto nível massivo). Após incluir a contribuição das variáveis do setor da matéria ('qui POT. m, 'teta POT. alfa', 'rô IND. alfa'), nós derivamos o espectro massivo da supercorda aberta. Embora os espinores puros sejam variáveis bosônicas, a função de partição dos espinores puros contém estados fermiônicos os quais começam aparecer a partir do segundo nível massivo. Estes estados fermiônicos vêm de funções que não são bem definidas globalmente no espaço dos espinores puros, e estão relacionados ao fantasma b no formalismo de spinores puros para a supercorda
Keywords: Supersimetria; Teoria das supercordas; Supersymmetry